2020
DOI: 10.1007/s00430-020-00679-x
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanins in the regulation of mast cell function

Abstract: Mast cells (MCs) are long-living immune cells highly specialized in the storage and release of different biologically active compounds and are involved in the regulation of innate and adaptive immunity. MC degranulation and replacement of MC granules are accompanied by active membrane remodelling. Tetraspanins represent an evolutionary conserved family of transmembrane proteins. By interacting with lipids and other membrane and intracellular proteins, they are involved in organisation of membrane protein compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…TM4SF1, a tumor-associated protein, is widely expressed in multiple human carcinomas, is localized at the surface of the cell membrane and late endocytic organelles, and plays a vital role in cell motility [44,45] . CD63 is an important activation marker for mast cells and is highly expressed on the surface of activated mast cells [46] . Several experiments have demonstrated that the expression of CD63 is inversely correlated with the motility of various cell types, while the overexpression of TM4SF1 can decrease the expression levels of CD63 on the cell surface, suggesting a potential mechanism for the activation and migration of mast cells [45,47] .…”
Section: Discussionmentioning
confidence: 99%
“…TM4SF1, a tumor-associated protein, is widely expressed in multiple human carcinomas, is localized at the surface of the cell membrane and late endocytic organelles, and plays a vital role in cell motility [44,45] . CD63 is an important activation marker for mast cells and is highly expressed on the surface of activated mast cells [46] . Several experiments have demonstrated that the expression of CD63 is inversely correlated with the motility of various cell types, while the overexpression of TM4SF1 can decrease the expression levels of CD63 on the cell surface, suggesting a potential mechanism for the activation and migration of mast cells [45,47] .…”
Section: Discussionmentioning
confidence: 99%
“…At the plasma membrane, they promote interactions with other membrane and intracellular proteins and lipids, to shape the organization of membrane domains. They are considered as “molecular facilitators” connecting extracellular and cytoplasmic signaling elements [ 47 ]. In this context, CD81 is known to facilitate cells adhesion or fusion in the frame of viral infection [ 48 , 49 ].…”
Section: Cd81 Biology Trafficking and Signalingmentioning
confidence: 99%
“…Axis. It was reported that changes in the MC microenvironment of the mouse peritoneum could lead to the alteration of the release of proteases, membrane signaling, and membrane receptor phenotype in MC [12]. We next attempted to examine tryptase granules by immunohistochemistry.…”
Section: Abdominal Massage Regulates the Trypase-par2-pkcεmentioning
confidence: 99%